Features of cognitive impairments in different mechanisms of mild traumatic brain injury: a literature review - Sarazhyna, Kateryna (The Ukrainian Scientific Medical Youth Journal, 2025)
іn wartime, a significant number of military personnel and civilians experience mild traumatic brain injuries, which negatively affect their quality of life, social adaptation, and recovery rates. Functional limitations caused by mild traumatic brain injuries impact cognitive, motor, communicative, and social domains. This review aims to explore the impact of mild traumatic brain injury on the development of cognitive dysfunctions through a biblio-systematic analysis of scientific literature. The study utilizes data from PubMed, Scopus, and Web of Science to investigate the effects of mild traumatic brain injury on cognitive impairments. The article analyzes various mechanisms of mild traumatic brain injuries and their impact on cognitive functions. It characterizes the types of cognitive and behavioral impairments resulting from mild traumatic brain injuries, such as decreased attention, memory deficits, impaired executive functions, and reduced processing speed. Special attention is given to blast-induced trauma, which amplifies the consequences of mild traumatic brain injuries through the primary effects of the blast wave. The literature analysis identified pathophysiological mechanisms, including metabolic cascades, structural brain damage, and neurotransmitter imbalances. A decrease in prefrontal cortex activity and disruptions in connectivity with other brain regions were observed. The study found that recovery dynamics in mild traumatic brain injuries patients vary depending on factors such as age, recurrent injuries, and psychological conditions. Comorbidities like depression, sleep disturbances, and chronic pain can exacerbate recovery outcomes, while the level of education serves as an important predictor of cognitive recovery. The effectiveness of diagnosis and rehabilitation during wartime relies on the implementation of a comprehensive approach, including screening tests, neuroimaging methods, and rehabilitation programs. The article provides an in-depth review of tests for memory, attention, and executive functions, such as the Psychomotor Vigilance Test, Rey Auditory Verbal Learning Test, and Stroop Test, as well as modern gamified rehabilitation programs like FitMi Home Therapy Program and ImPACT, which combine physical and cognitive exercises. Future research should focus on the development and improvement of methods for monitoring the condition of patients after mild traumatic brain injury, as well as the creation and adaptation of cognitive testing scales and programs for Ukraine. The primary aim is to enhance the quality of life of military personnel, facilitate their social adaptation, accelerate recovery after injury, and develop individualized rehabilitation programs.